The measurement of functioning using the International Classification of Functioning, Disability and Health: comparing qualifier ratings with existing health status instruments. Issue 5 (27th February 2019) - Prodinger, Birgit; Stucki, Gerold; Coenen, Michaela; Tennant, Alan
Abstract: Background: The International Classification of Functioning, Disability and Health is the international standard for describing and monitoring functioning. While the categories, the units of the classification, were not designed with measurement in mind, the hierarchical structure of the classification lends itself to the possibility of summating categories into some higher order domain. Focusing on the chapters of d4 Mobility, d5 Self-Care and d6 Domestic Life, this study seeks to ascertain if qualifiers rating of categories (0-No problem to 4-Complete problem) within those chapters can be summated, and whether such derived measurement is consistent with estimates obtained from well-known instruments which purport to measure the same constructs. Methods: The current study applies secondary analysis to data previously collected in the context of validating Core Sets for stroke, rheumatoid arthritis, and osteoarthritis. Data included qualifier-based ratings of the categories in the Core Sets, and the physical functioning sub-scale of the Short-Form 36, and the World Health Organization Disability Assessment Schedule 2.0. To examine qualifier-comparator scale item agreement Kappa statistics were used. To identify whether appropriate gradients of the comparator scales were observed across qualifier levels, an Independent Sample Median Test of the ordinal scores was deployed. To investigate the internal validity of the summated ICF categories, the Rasch model was applied. Results: Data from 2, 927 subjects from Europe, Australasia, Middle East and South America were available for analysis; 36.3% had experienced a stroke, 35.8% osteoarthritis, and 27.9% had rheumatoid arthritis. The items from the Short-Form 36 could not match directly the qualifier categories as the former had only 3 response options. The Kappa between World Health Organization Disability Assessment Schedule 2.0 items and categories was low. For all qualifiers, a significant (<0.001) overall gradient was observed across the comparator scales. Only in few of the World Health Organization Disability Assessment Schedule 2.0 items could no discrete level be detected. The aggregation of the qualifiers at the Chapter and higher order levels mostly revealed fit to the Rasch model. Almost all ICF qualifiers showed ordered thresholds suggesting that the current structure and response options of the qualifiers worked as intended. Conclusions: The findings of this study provide supporting evidence for the use of the professionally rated categories and associated qualifiers to measure functioning. Implication for Rehabilitation: This study provides evidence that functioning data can be collected directly with the International Classification of Functioning, Disability and Health (ICF) by using the ICF categories as items and the ICF qualifiers as rating scale. The findings of this study show the aggregated ratings of ICF categories from the chapters d4 Mobility, d5 Self-care, and d6 Domestic life capture a broader spectrum of the construct than the corresponding summated items from the SF36-Physical Function sub-scale and the corresponding items of the World Health Organization Disability Assessment Schedule 2.0. This study illustrates the potential of building quantitative measurement by aggregating ICF categories and their qualifier ratings into meaningful domains.